Delayed feedback control of unstable steady states with high-frequency modulation of the delay - GJurchinovski, Aleksandar; Jüngling, Thomas; Urumov, Viktor; Schöll, Eckehard (My University, 2013)
We analyze the stabilization of unstable steady states by delayed feedback control with a periodic time-varying delay in the regime of a high-frequency modulation of the delay. The average effect of the delayed feedback term in the control force is equivalent to a distributed delay in the interval of the modulation, and the obtained distribution depends on the type of the modulation. In our analysis we use a simple generic normal form of an unstable focus, and investigate the effects of phase-dependent coupling and the influence of the control loop latency on the controllability. In addition, we have explored the influence of the modulation of the delays in multiple delay feedback schemes consisting of two independent delay lines of Pyragas type. A main advantage of the variable delay is the considerably larger domain of stabilization in parameter space.
Keywords: Nonlinear Sciences - Chaotic Dynamics; Nonlinear Sciences - Chaotic Dynamics